MANAJEMEN PENDIDIKAN KARAKTER PADA PEMBELAJARAN IPS - Eka Puspareni (UNIVERSITAS BENGKULU, 2016)
The objective of this research is to describe the management program of character education on Social Learning at State Junior High School 1 Bermani Ilir of Kepahiang inplanning, implementation, evaluation, advance reaction factors that found and problem solving to solve this matter. The method of this research was descriptive qualitative. Data collecting use interview, observation and documentation. The result of this research indicates that the management of character education program on Social Learning at State Junior High School 1 Bermani Ilir of Kepahiang has been done properly to the management program although that’s still need to develop continuously. The problem majority at skill and knowledge of teacher need more education about character building for student if they want to success on managementcharacter education on social learning.Key Words: education management, character education, social learning